2012
DOI: 10.2478/s11687-012-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Ascaris suum in slaughter pigs during 2000–2009 in Slovakia

Abstract: 221 SummaryAscaris suum is a parasitic nematode of pigs with worldwide distribution causing economic loses due do health interactions, reduced feed to gain efficiency and loses due to liver condemnation at abattoirs. To survey the herd prevalence of ascariosis in Slovakia, the presence of milk spots in liver of slaughtered pigs is monitored at abattoirs. According to shortened life-span of fattening pigs, this is the most suitable screening method for efficiency evaluation of control measures. Within the monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…(Giese et al., 1973; Laber et al., 2002), Ascarid spp. (Midttun et al., 2018; Ondrejková et al., 2012) are found to be associated with severe morbidity and mortality in pigs. Ascaris suum , Strongyloides , Trichuris suis and Strongyle have previously been reported from pigs in Nepal (Baskota & Shrestha, 2019; Sah, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…(Giese et al., 1973; Laber et al., 2002), Ascarid spp. (Midttun et al., 2018; Ondrejková et al., 2012) are found to be associated with severe morbidity and mortality in pigs. Ascaris suum , Strongyloides , Trichuris suis and Strongyle have previously been reported from pigs in Nepal (Baskota & Shrestha, 2019; Sah, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Sanchez-Vazquez et al (2010) recently demonstrated that infection by this parasite can decrease the animal's daily weight gain by up to 10%, and the feed conversion of pigs by up to 13% in the growing phase and at slaughter. A high occurrence of the parasite has also been reported in the herds of several countries, such as Slovakia, England and Poland (ČERNEK et al, 2012;SANCHEZ-VAZQUEZ et al, 2012;KNECHT et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Monitoring during slaughter allows for fast and inexpensive evaluation of herd health (ČERNEK et al, 2012), which in turn allows for the estimation of economic losses based on the number of discarded organs and on the number of infected animals. Sanchez-Vazquez et al (2010) recently demonstrated that infection by this parasite can decrease the animal's daily weight gain by up to 10%, and the feed conversion of pigs by up to 13% in the growing phase and at slaughter.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, a survey of the six largest abattoirs demonstrated a rate of 2.5 to 6.5 percent milk spots in 729 herds (Lundeheim 2010). In Slovakia, 19,017 animals from 279 herds were inspected from 2000 to 2009 and a decrease in milk spot rates was seen from 39.5 to 6.9 percent (Ondrejková 2012). The authors attributed this decline to an increasing positive attitude toward parasite control within the Slovakian swine industry.…”
Section: Prevalencementioning
confidence: 99%